Archives of Conjure: Stories of the Dead in Afrolatinx Cultures - Otero, Solimar (Gender, Theory, and Religion, 2020)
Intro -- Table of Contents -- Acknowledgments -- Introduction: Archives of Conjure -- 1. Residual Transcriptions -- 2. Crossings -- 3. Flows -- 4. Sirens -- Conclusion: Espuma del Mar, Sea- Foam -- Notes -- References -- Index.